Double-Blind, Randomized Study of the Efficacy and Safety of Oral Pharmacokinetically Enhanced Amoxicillin-Clavulanate (2,000/125 Milligrams) versus Those of Amoxicillin-Clavulanate (875/125 Milligrams), Both Given Twice Daily for 7 Days, in Treatment of Bacterial Community-Acquired Pneumonia in Adults - File, T. M. (American Society for Microbiology, 2004)
This randomized, double-blind, noninferiority trial was designed to demonstrate that pharmacokinetically enhanced amoxicillin-clavulanate (2,000/125 mg) was at least as effective clinically as amoxicillin-clavulanate 875/125 mg, both given twice daily for 7 days, in the treatment of community-acquired pneumonia in adults. In total, 633 clinically and radiologically confirmed community-acquired pneumonia patients (intent-to-treat population) were randomized to receive either oral amoxicillin-clavulanate 2,000/125 mg (n = 322) or oral amoxicillin-clavulanate 875/125 mg (n = 311). At screening, 160 of 633 (25.3%) patients had at least one typical pathogen isolated from expectorated or invasive sputum samples or blood culture (bacteriology intent-to-treat population). Streptococcus pneumoniae (58 of 160, 36.3%), methicillin-susceptible Staphylococcus aureus (34 of 160, 21.3%), and Haemophilus influenzae (33 of 160, 20.6%) were the most common typical causative pathogens isolated in both groups in the bacteriology intent-to-treat population. Clinical success in the clinical per protocol population at test of cure (days 16 to 37), the primary efficacy endpoint, was 90.3% (223 of 247) for amoxicillin-clavulanate 2,000/125 mg and 87.6% (198 of 226) for amoxicillin-clavulanate 875/125 mg (treatment difference, 2.7; 95% confidence interval, −3.0, 8.3). Bacteriological success at test of cure in the bacteriology per protocol population was 86.6% (58 of 67) for amoxicillin-clavulanate 2,000/125 mg and 78.4% (40 of 51) for amoxicillin-clavulanate 875/125 mg (treatment difference, 8.1%; 95% confidence interval, −5.8, 22.1). Both therapies were well tolerated. Amoxicillin-clavulanate 2,000/125 mg twice daily was shown to be as clinically effective as amoxicillin-clavulanate 875/125 mg twice daily for 7 days in the treatment of adult patients with community-acquired pneumonia, without a noted increase in the reported rate of adverse events.